EXPERIENCE IN BIOGRAPHICAL COMPILATION OF MEDIAEVAL DAGESTAN SCHOLARS: A CASE STUDY OF MUHAMMAD AL-IRI (17TH CENTURY) - Karimov, Magomedarip Omarashabovic; Malamagomedov, Dzamaludin Murtazalievic (History, Archeology and Ethnography of the Caucasus, 2024)
This study examines the previously unexplored life and works of Muhammad b. ‘Umar ad-Dagistani al-‘Iri, a 17th-century scholar from Dagestan. His authorship of the Arabic hagiographic treatise “Khazihi risala al-jinn” (1668) is well-established. By examining the colophon of a manuscript copied by his father in 1633, this research unveils the scholar’s origins. Additionally, several manuscripts he copied during his studies and travels through the Middle East have been identified. By analyzing them, the research unveils his academic background, including the range of disciplines and textbooks studied, as well as his scope of interests. We’ve uncovered a written source – the memoirs of Muhammad al-‘Iri, written in the genre of edification. Within these memoirs, the author recounts his experiences in Shemakha, Erzurum, Damascus, Mecca, and other cities visited during his pilgrimage to Mecca. He also provides the names of numerous theologians and intellectuals from various regions of the Ottoman Empire whom he encountered during his travels. The research concludes that Muhammad al-‘Iri was born in the 1620s and likely passed away around 1680. Through extensive study and travel in the Middle East, he developed expertise in logic, Islamic jurisprudence, history, and notably, hagiography.
Keywords: Dagestan; Muhammad al-‘Iri; biography; hagiography; colophon; Arabic manuscript